Directional Transformation of Heterometallic Oxo Clusters: A New Approach to Prepare Wide‐Bandgap Cathode Interlayers for Perovskite Solar Cells. (3rd March 2023) - Xiao, Guo‐Bin; Mu, Xijiao; Zhou, Shuyu; Zhu, Liu; Peng, Yong; Liang, Qing; Zou, Xiaoxin; Zhang, Jian; Zhang, Lei; Cao, Jing
Abstract: Typical wide‐band gap cathode interlayer materials are difficulty in reducing interface recombination without limiting charge transport in perovskite solar cells (PSCs). Here, a lead‐doped titanium‐oxo cluster protected by S‐containing ligands is introduced at the interface of perovskite and SnO2 . By in situ heating, the cluster is transformed into PbSO4 ‐PbTi3 O7 heterostructure. The oxygen atoms from sulfate ion in heterostructure connect with iodine from perovskite to boost interfacial electron extraction and reduce charge recombination. While the yielded metallic interface between PbSO4 and PbTi3 O7 promotes the electron transport across the interface. Finally, an efficiency as high as 24.2 % for the modified PSC is obtained. The heterostructure well‐stabilize the interface of perovskite and SnO2, to greatly improve the device stability. This work provides a novel strategy to prepare wide‐band gap cathode interlayer by directional transformation of heterometallic oxo clusters. Abstract : A lead‐doped titanium‐oxo cluster protected by sulfur‐containing organic ligands is employed as a molecular model to realize the directional preparation of PbSO4 ‐PbTi3 O7 heterostructure at the cathode interlayer in perovskite solar cells (PSCs). The oxygen atoms from the sulfate ion in the heterostructure connect with iodine from the perovskite to boost interfacial electron extraction and reduce charge recombination. An efficiency as high as 24.2 % for the modified PSC is realized, and the stability of the devices is also improved.